2016
DOI: 10.1093/bja/aev255
|View full text |Cite
|
Sign up to set email alerts
|

Neuraxial block and postoperative epidural analgesia: effects on outcomes in the POISE-2 trial

Abstract: Neuraxial block and postoperative epidural analgesia were not associated with adverse cardiovascular outcomes among POISE-2 subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Interestingly, the overwhelming majority decides for or against advanced instrumentation on a case‐by‐case basis. These findings are highly relevant as sympatholysis with subsequent hemodynamic deterioration frequently occurs with EA and can be anticipated 35 . Additionally, since combined GA and EA is recommended particularly for major surgery, advanced hemodynamic monitoring and instrumentation is usually indicated anyway.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the overwhelming majority decides for or against advanced instrumentation on a case‐by‐case basis. These findings are highly relevant as sympatholysis with subsequent hemodynamic deterioration frequently occurs with EA and can be anticipated 35 . Additionally, since combined GA and EA is recommended particularly for major surgery, advanced hemodynamic monitoring and instrumentation is usually indicated anyway.…”
Section: Discussionmentioning
confidence: 99%
“…Using data from the POISE-2 trial, a large multicentre study that randomized high-risk surgical patients to aspirin or placebo and to clonidine or placebo, Leslie and colleagues 15 compared outcomes among study patients who did and did not receive neuraxial blocks as part of their anaesthesia care. Leslie and colleagues 15 found no statistically significant association between the receipt of any intraoperative neuraxial block and the odds of death, myocardial infarction, or stroke at 30 days, although a subgroup analysis did find spinal anaesthesia alone to be associated with lower odds of death or non-fatal myocardial infarction than general anaesthesia alone. A smaller accompanying analysis found no statistically significant association between postoperative epidural analgesia and death, myocardial infarction, or stroke.…”
Section: Referencesmentioning
confidence: 97%
“…Ultimately, the work presented here by Leslie and colleagues 15 is important both as a source of insight regarding the potential risks and benefits of neuraxial techniques and as an occasion to consider the types of insights that available research in this area has yet to provide. As such, it should prompt us not only to debate the implications of their findings for clinical practice and policy, but also to engage in mapping out the key questions in this area that remain to be answered by randomized trials, and to start to think through the advantages and disadvantages of different trial designs for answering these questions.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…commonest co-morbid condition found in A multinational study on the effects of neuraxial preoperative patients presenting for elective block and postoperative epidural analgesia on procedures (3). cardiovascular morbidity and mortality concluded Low ejection fraction often times results from that there is reduced cardiovascular complications long standing, poorly controlled hypertension, (10), even though another study indicated no diabetes and coronary artery diseases. Assessment of reduction in overall mortality (11).…”
Section: Introductionmentioning
confidence: 99%